Efficacy, tolerability, and retention of antiseizure medications in PRRT2-associated infantile epilepsy - Driedger, Jan Henje; Saffari, Afshin; Bast, Thomas; Brockmann, Knut; Ehrhardt, Laura; Fazeli, Walid; Janzarik, Wibke G.; Klabunde-Cherwon, Annick; Kluger, Gerhard; Muhle, Hiltrud; Pendziwiat, Manuela; Møller, Rikke S.; et al. (Neurology. Genetics, 2022)
Background and Objectives Pathogenic variants in PRRT2, encoding for the proline-rich transmembrane protein 2, were identified as the main cause of self-limiting sporadic and familial infantile epilepsy. Reported data on treatment response to antiseizure medications (ASMs) in defined monogenic epilepsies are limited. The aim of this study was to evaluate the treatment response of ASMs in children with monogenic PRRT2-associated infantile epilepsy. - Methods A multicenter, retrospective, cross-sectional cohort study was conducted according to the Strengthening the Reporting of Observational Studies in Epidemiology criteria. Inclusion criteria were occurrence of infantile seizures and genetic diagnosis of likely pathogenic/pathogenic PRRT2 variants. - Results Treatment response data from 52 individuals with PRRT2-associated infantile epilepsy with a total of 79 treatments (defined as each use of an ASM in an individual) were analyzed. Ninety-six percent (50/52) of all individuals received ASMs. Levetiracetam (LEV), oxcarbazepine (OXC), valproate (VPA), and phenobarbital (PB) were most frequently administered. Sodium channel blockers were used in 22 individuals and resulted in seizure freedom in all but 1 child, who showed a reduction of more than 50% in seizure frequency. By contrast, treatment with LEV was associated with worsening of seizure activity in 2/25 (8%) treatments and no effect in 10/25 (40%) of treatments. LEV was rated significantly less effective also compared with VPA and PB. The retention rate for LEV was significantly lower compared with all aforementioned ASMs. No severe adverse events were reported, and no discontinuation of treatment was reported because of side effects. - Discussion In conclusion, a favorable effect of most ASMs, especially sodium channel blockers such as carbamezepine and OXC, was observed, whereas the efficacy and the retention rate of LEV was lower in PRRT2-associated childhood epilepsy. Tolerability in these young children was good for all ASMs reported in the cohort. - Classification of Evidence This study provides Class IV evidence that in individuals with PRRT2-associated infantile epilepsy, sodium channel blockers are associated with reduced seizure frequency but levetiracetam is not.
First published September 28, 2022
Gesehen am 25.01.2023